2021
DOI: 10.3329/ajmbr.v7i3.56137
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp farming in Southwestern Bangladesh: a case study of economic impacts during COVID-19

Abstract: Bangladesh is endowed with a long coastline and therefore offers the enormous potential of marine wealth. In the coastal part of Bangladesh, shrimp is one of the most important export-oriented aquacultures due to high-profit return on the same value. Shrimp farming contributes significantly to the livelihoods of rural Bangladeshis in the southwestern region. It is critical to be aware of current culture practices and the measures shrimp farmers take to sustain the trend of exporting shrimp around the world. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Rafiquzzaman ( 2020 ), Islam et al ( 2021 ), and Lebel et al ( 2021 ) reported similar situations for Bangladesh and the Mekong Region, where the lockdown forced by the pandemic led to consumption and price reduction of aquaculture products. During the pandemic, the low market shrimp price has been deemed the major issue for shrimp farmers in Southwestern Bangladesh (Akter and Khan, 2021 ). However, this investigation found that during the pandemic, shrimp prices recovered in November and exceeded those observed in the previous years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rafiquzzaman ( 2020 ), Islam et al ( 2021 ), and Lebel et al ( 2021 ) reported similar situations for Bangladesh and the Mekong Region, where the lockdown forced by the pandemic led to consumption and price reduction of aquaculture products. During the pandemic, the low market shrimp price has been deemed the major issue for shrimp farmers in Southwestern Bangladesh (Akter and Khan, 2021 ). However, this investigation found that during the pandemic, shrimp prices recovered in November and exceeded those observed in the previous years.…”
Section: Discussionmentioning
confidence: 99%
“…A sectoral assessment of the pandemic impact on aquaculture in India was conducted by Kumaran et al ( 2021 ). Akter and Khan ( 2021 ) showed shrimp farming as a case study of the pandemic economic impacts on southwestern Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Respondents faced these problems mainly due to restriction in importing seed production, the supply of farm inputs, processing and marketing of shrimp. According to [20] investigated the most common issue of low market pricing which was the source of concern for shrimp farmers, especially in the wake of the pandemic similarly shrimp prices in the local and worldwide markets fluctuate dramatically because of inconsistencies in the supply chain [21]. On the other hand, consumers are paying more money for aquatic products but dealers pay less to buy these products from farmers [22].…”
Section: Problems In Marketingmentioning
confidence: 99%